Energy Efficient Homes: Fluorescent Lighting - Hyun-Jeong Lee; Kathleen C. Ruppert; Wendell A. Porter (EDIS)
FCS-3270, a 6-page fact sheet by Hyun-Jeong Lee, Kathleen C. Ruppert, and Wendell A. Porter, is part of the Energy Efficient Homes series. It defines fluorescent lighting terms and answers many questions homeowners might have about compact fluorescent lighting. Includes references. Published by the UF Department of Family, Youth and Community Sciences, June 2008.